2004
DOI: 10.1039/b405753h
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cu2+ions with chicken prion tandem repeats

Abstract: The potentiometric and spectroscopic (EPR, UV-Vis, CD) data have shown that the chicken prion hexa-repeat (Ac-His-Asn-Pro-Gly-Tyr-Pro-NH(2)) is a very specific ligand for Cu(2+) ions. The His imidazole is an anchoring binding site, then the adjacent amide nitrogen coordinates as a second donor. The presence of Pro at position 3 induces binding of phenolate oxygen as a third donor atom. The tridentate coordination dominates around physiological pH. Similar to human octapeptide fragments, chicken tandem repeats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
44
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 20 publications
16
44
2
Order By: Relevance
“…Comparison of the binding abilities between demegens and hexapeptides from chicken prion proteins allowed also to make some suggestions (Fig. 18C-E) [42]. Trimeric peptide (3-Hex) at low pH range exhibits the multi-imidazolic coordination mode and forms more stable complexes with Cu 2+ ion than Ac-DMG-NH 2 .…”
Section: Coordination Properties Of Demegen P-113 Towards Cu 2+ Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the binding abilities between demegens and hexapeptides from chicken prion proteins allowed also to make some suggestions (Fig. 18C-E) [42]. Trimeric peptide (3-Hex) at low pH range exhibits the multi-imidazolic coordination mode and forms more stable complexes with Cu 2+ ion than Ac-DMG-NH 2 .…”
Section: Coordination Properties Of Demegen P-113 Towards Cu 2+ Ionsmentioning
confidence: 99%
“…The coordination pattern of chicken hexapeptide depends strongly on the number of hexapeptide units. Single hexapeptide unit binds copper ion in the physiological pH by {N im , N − } donor sets in the main trans/trans amide bond isomer [42][43][44]. The involvement of the consecutive amide nitrogen atoms in metal ion chelatation is disrupted by the presence of Pro residue between Asn and Gly residues.…”
Section: Chicken Prion Proteinmentioning
confidence: 99%
“…Increasing the copper amount, the copper(II) is bound to each octa-repeat by means of one imidazole nitrogen, two amide nitrogens from the two glycine residues and one carbonyl oxygen [128][129][130]. Although it has been reported that the tetrahexarepeat peptide can bind up to four copper atoms, being in this similar to human PrP C even if with a lower affinity [133], other results questioned this finding [87,132,137]. UV-vis and CD studies carried out on chicken hexameric peptide fragments containing two histidine residues indicate that this peptide binds only one copper(II), evidencing the significant role of Gly residues in copper coordination for the mammalian octameric region [132].…”
Section: Prion and Copper(ii) Coordination Features: Mammal Vs Avianmentioning
confidence: 99%
“…Copper complex species with chPrP C peptide fragments show binding constant values [84,87,[133][134][135]140] lower than those found in SOD-1 enzymes. This appears in contrast with the biological significance of a true SOD-like enzyme in vivo, which has to bind strongly the metal ion.…”
mentioning
confidence: 99%
“…The molar ratio 1:1 was not studied due to the tendency of lanthanide ions to achieve high coordination numbers, and inadequate number of donor atoms of the ligand. Determined pK w for dimethyl sulfoxide/ water (30:70) was 14.501 [31]. The protonation constants of the N,N'-bis(5-methylsalicylidene)-4-methyl-1,3-phenylenediamine, the selection of the models as well as the stability constants of the complexes were determined with HYPER-QUAD software which uses the nonlinear method of least squares [32].…”
Section: Introductionmentioning
confidence: 99%